Anastrepha species (Diptera: Tephritidae), their host plants and parasitoids (Hymenoptera) in the state of Roraima, Brazil: state of the art - Alberto Luiz Marsaro Júnior; Ricardo Adaime; Beatriz Ronchi-Teles; Miguel Francisco Souza-Filho; Paulo Roberto Valle da Silva Pereira; Elisângela Gomes Fidelis de Morais; Rinaldo Joaquim Silva Júnior; Elizana Silva e Silva (Biotemas)
The aim of this review was to update the available information on Anastrepha species in the state of Roraima, Brazil, with emphasis on distribution, host plants and parasitoids. In total, 25 species of Anastrepha and 27 host plant species have been recorded to date in Roraima. Anastrepha striata and A. obliqua are widely distributed in the state. Anastrepha obliqua is the most polyphagous species, where it is associated with 13 hosts. Six species of parasitoids of Anastrepha have been reported in Roraima. Of these, Doryctobracon areolatus is the most abundant and has been associated with the largest number of Anastrepha species.